Thermal insulation handbook for the oil, gas, and petrochemical industries - Bahadori, Alireza (Elsevier, 2014)
Thermal Insulation Handbook for the Oil and Gas Industries addresses relative design, materials, procedures, and standard installation necessities for various oil and gas infrastructure such as pipelines, subsea equipment, vessels, and tanks. With the continued increase in available natural gas ready to export -- especially LNG -- and the definition of "deepwater" changing every year, an understanding of thermal insulation is more critical than ever. This one-of-a-kind handbook helps oil and gas engineers ensure that their products are exporting safely and that the equipment's integrity is protected. Topics include: Design considerations and component selection, including newer materials such as cellular glass Methods to properly install the insulation material and notable inspection and safety considerations in accordance with applicable US and international standards, specifically designed for the oil and gas industry Calculations to make sure that every scenario is considered and requirements for size, composition, and packaging are met effectively Understand all appropriate, new and existing, insulation material properties as well as installation requirements Gain practical knowledge on factors affecting insulation efficiency, rules of thumb, and links to real-world case studies Maximize flow assurance safely and economically with critical calculations provided